A Cross-Sectional Study of Intestinal Parasitic Infections in a Rural District of West China. (1st June 2003) - Tang, Ning; Luo, Nian Ji
Abstract : BACKGROUND: Parasitic infections are widespread in rural areas of West China. The remote and humid environment, traditional ways of life, contaminated potable water and limited health services all contribute to the transmission and persistence of fecal parasites. OBJECTIVE: To describe the prevalence of intestinal parasitic infections in an area of West China, including its associations with demographic variables. METHODS: Single fecal specimens were collected using a previously validated kit. Parasites were detected microscopically by iodine-stained smear, modified Kato-Katz thick smear, simple saline smear, test tube filter paper culture and adhesive cellophane tape anal swab. RESULTS: The prevalence of enteric parasites in the population was 51.7%. The proportion of individuals infected with one parasite was 36.5%, two parasites 12.7%, three parasites 3.0% and four parasites 0.08%. Parasites identified included Ascaris lumbricoides in 41.4% of all individuals tested, Ancylostoma duodenale in 17.7%, Trichurias trichuria in 8.25%, Enterobius vermicularis in 0.43%, Blastocystis hominis in 1.37%, Entamoeba coli in 0.47%, Entamoeba histolytica in 0.16%, Giardia lamblia in 0.04%, Strongyloides stercoralis in 0.04% and Clonorchis sinensis in 0.04%. The prevalence was significantly increased in women, people aged 15 to 19 years and over 80 years, the rural farm population, farmers, preschool and primary school groups, residents of a hilly rather than mountainous or plains terrain, and in intermediate income groups. The prevalence was significantly negatively associated with educational level, but not with age or income. CONCLUSIONS: This study supports the use of simple fecal examinations to monitor the parasite burden in rural areas of developing countries. Enteric parasites remain common in this population in rural China.